Land Utilization Efficiency of Corn and Black Soybean Intercropping System on Ultisoll with Various Doses of Cow Dung Fertilizer and Weeding Frequency - Anisha, Sukma Dwi Nur; Turmudi, Edhi; Chozin, Mohammad (TERRA : Journal of Land Restoration, 2024)
The narrow land ownership status among farmers poses challenges for agricultural production, despite the increasing demand for agricultural products in both quantity and variety. To address this issue, intercropping—a planting system that involves cultivating multiple crop types simultaneously—has been employed. This system enhances land productivity, reduces farming risks, and ensures income sustainability for farmers. Corn and black soybeans are ideal crops for intercropping due to their mutually beneficial interactions. Key factors influencing the success of this system include the frequency of weeding and the application of cow dung fertilizer. This study aimed to identify the optimal dose of cow dung fertilizer and weeding frequency to achieve the highest crop yield and land use efficiency in a corn-black soybean intercropping system. Conducted from February to May 2021 in Pematang Gubernur Village, Bengkulu City, the experiment employed a Split Plot Design within a Complete Randomized Block Design (RCBD) with two factors and three replications. The main plot consisted of three weeding frequencies: no weeding, weeding once (2 WAP), and weeding twice (2 and 5 WAP). Subplots included cow dung fertilizer doses: 0, 5, 10, and 15 tons ha-1. Results indicated the highest sunlight utilization efficiency occurred with 2x weeding and 5–10 tons ha-1 of cow dung fertilizer. Land use efficiency (LER > 1) was achieved under these conditions, while black soybean generally exhibited lower light efficiency. These findings highlight the importance of proper weeding and fertilization practices to optimize land use, providing valuable insights for sustainable farming strategies in regions with limited arable land.